To solve the equation 7(x - 8) = 49 for x, the first step is to simplify the equation by applying the distributive property or by dividing both sides of the equation by 7 to isolate the term containing x. However, dividing by 7 is the shorter initial step, so we'll proceed with that:
Divide both sides of the equation by 7 to isolate (x - 8):
7(x - 8) / 7 = 49 / 7
This simplifies to:
x - 8 = 7
Now you have a simpler equation where x is only one step away from being isolated. The next step after that would be to add 8 to both sides of the equation to solve for x:
x - 8 + 8 = 7 + 8
x = 15
Hence, the value of x that satisfies the original equation 7(x - 8) = 49 is 15.
Identify the first step in solving this equation for x: 7(x-8)=49
1 answer